2006
DOI: 10.1111/j.1471-0528.2006.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Referral and attendance at a specialist antenatal clinic: qualitative study of women’s views

Abstract: Objective To explore women's views on being referred to and attending a specialist antenatal hypertension clinic.Design Qualitative interview study.Setting A pregnancy hypertension clinic in a large teaching hospital in the East Midlands.Population Twenty-one women (aged 18 years and above) attending the pregnancy hypertension clinic for the first time during their current pregnancy.Methods Women who had been referred to and attended a specialist antenatal clinic participated in semi-structured interviews. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Jackson et al. ’s 23 qualitative study of women’s attendance at ante‐natal clinic showed that the mothers found accessing the clinic as anxiety‐provoking and ‘distressing’. Moreover, in this study, the parents’ did not wish their own fears to be communicated to their children 24 and this may have contributed to their view that they were not candidates for dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Jackson et al. ’s 23 qualitative study of women’s attendance at ante‐natal clinic showed that the mothers found accessing the clinic as anxiety‐provoking and ‘distressing’. Moreover, in this study, the parents’ did not wish their own fears to be communicated to their children 24 and this may have contributed to their view that they were not candidates for dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Providers' behaviour is considered influenceable via, for example, education [97,[119][120][121], and guidelines [19,97,115,122]. Women bring in factors such as timing of presentation, sense of control, views and beliefs, sense of safety, perceived norms, perceived availability of options, and demographic characteristics such as age, level of educational and income [114,115,[123][124][125][126][127][128][129][130]. Because a consulting care provider either needs additional resources or does not, the decision to refer is inherently a "threshold phenomenon" [108].…”
Section: Risk Selection As a Practice: Detecting And Assessing Risk mentioning
confidence: 99%
“…However, the trials included in the review included no information on psychological outcomes for women. Some studies have suggested that whilst some pregnant women welcome referral to a specialist clinic during pregnancy, others experience it as unsettling (Jackson 2006). Any future research in this area should examine which aspects of service provision are preferred by women.…”
Section: Authors’ Conclusionmentioning
confidence: 99%
“…The package of care offered in such clinics may include promising prophylactic interventions for labour prevention including progesterone, clindamycin or cervical cerclage (Althuisius 1998; Da Fonesca 2003; Ugwumadu 2003). However, stress has been associated with enhanced risk of preterm delivery and there is evidence that, whilst some pregnant women welcome referral to a specialist clinic during pregnancy, others experience it as unsettling (Jackson 2006).…”
Section: Introductionmentioning
confidence: 99%